The Face of Discrimination in Javanese Language Learning in Elementary School Students - Maruti, Endang Sri (Nexus Publishing, 2024)
This research aims to provide an overview of the forms of discrim- ination in Javanese language learning during the Covid-19 pan- demic which has hit for almost the last 2 years. This research is a descriptive qualitative type based on 4 cases of Javanese lan- guage learning in elementary schools, especially those in the Ma- diun City area. The data for this research are various forms of discrimination found in WhatsApp Group conversations between teachers and students, activities on Google Classroom, Javanese language textbooks, as well as the results of interviews with teachers and parents. The results of the research show that in learning Javanese, especially in elementary schools, there are 4 forms of discrimination, namely learning Javanese as local con- tent, Javanese being taught by class teachers who are not gradu- ates of Javanese language education, in online learning there are never synchronous meetings held, the only form of learning is lim- ited to giving assignments without any explanation of the mate- rial. Keywords: educational oppression, Javanese language learning, elementary school